Using Focus Group Interviews for Planning or Evaluating Extension Programs - Glenn D. Israel; Sebastian Galindo-Gonzalez (EDIS)
Revised! AEC-387, a 6-page illustrated fact sheet by Glenn D. Israel and Sebastian Galindo-Gonzalez, provides a brief overview of the focus group interview and suggestions for conducting such interviews. Published by the UF Department of Agricultural Education and Communication, May 2008.